2016
DOI: 10.1002/j.1681-4835.2016.tb00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability and Information Practices among (Undocumented) Latino Migrants

Abstract: This paper explores the information practices (information seeking, using, and sharing) among Latino migrants, particularly undocumented migrants, in three different settings: at the US-Mexico border, in Seattle, Washington, and in Cali, Colombia. Through participatory photography and unstructured interviews, we explore the life experiences and information practices of marginalized and underserved communities and relate them to their experience of transience through different stages of the migration experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Lloyd and Wilkinson found that photographs illuminated the everyday spaces in which participants searched for and made sense of information. Gomez (2016) employed participatory photography to explore the information practices among migrants along the US-Mexico border, in Seattle, and in Southern Colombia, finding that the method empowered participants to disrupt preconceived notions about the research topics and promoted deeper understandings of participants' lived realities.…”
Section: Methodsmentioning
confidence: 99%
“…Lloyd and Wilkinson found that photographs illuminated the everyday spaces in which participants searched for and made sense of information. Gomez (2016) employed participatory photography to explore the information practices among migrants along the US-Mexico border, in Seattle, and in Southern Colombia, finding that the method empowered participants to disrupt preconceived notions about the research topics and promoted deeper understandings of participants' lived realities.…”
Section: Methodsmentioning
confidence: 99%
“…The literature is uneven about whether the overall digital divide is widening or narrowing. However, the literature is consistent about gaps in desirable digital accessibility, especially amongst vulnerable populations like international migrants (Gomez et al, 2019;Nogueron-Liu, 2016). To this extent, organizations should consider developing multi-level, culturally sensitive approaches, especially for vulnerable populations (Lyons et al, 2019).…”
Section: The Great Digital Divide?mentioning
confidence: 99%
“…Digital spaces, however, pose concerns for a diminished sense of community and heightened risks of breaches in data privacy (Harlow & Guo, 2014;Gomez, 2019). Several studies examine the intersection between data privacy and vulnerable migrants.…”
Section: The Great Digital Divide?mentioning
confidence: 99%
See 1 more Smart Citation
“…Our past research is particularly focused on undocumented migration into the United States across the country's southern border with Mexico and, to a lesser extent, migrant integration into various communities in the United States. The primary empirical research we reflect on here is drawn from three interrelated lines of research: the first was a study of the migration-related information practices of clandestine migrants in a shelter in Nogales, Sonora, Mexico (Newell, Gomez and Guajardo 2016;Newell, Gomez and Guajardo 2017;Newell and Gomez 2015;Yefimova et al 2015); the second was a study of the information practices of Latino migrants, many of whom were undocumented, at the US-Mexico border, in Seattle, Washington, and in Cali, Colombia Gomez 2016;Gomez and Vannini 2015;Vannini, Gomez and Guajardo 2016); and the third was a study of the information practices of the humanitarian migrant-aid organizations that work to serve and support clandestine and undocumented migrants in and around Nogales, Sonora, and Nogales, Arizona (Gomez, Newell and Vannini 2020;Vannini, Gomez and Newell 2019;.…”
Section: Introductionmentioning
confidence: 99%